1976
DOI: 10.1111/j.1744-7348.1976.tb01679.x
|View full text |Cite
|
Sign up to set email alerts
|

Growth and development of soyabean cv. TK5 as affected by tropical daylengths, day/night temperatures and nitrogen nutrition

Abstract: S U M M A R YTwo experiments were done in Saxcil growth cabinets in order to investigate the effects of climatic factors and nitrogen nutrition on the growth, reproductive development and seed yield of soyabean cv. TKg. In the first, plants were grown to maturity in eight environments comprising all combinations of two short daylengths (I I h 40 min and 13 h 20 min), two day (27 and 33 "C) and two night (19 and 24 "C) temperatures. In the second, day temperature was kept at 33 "C but the night temperature was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
34
2
1

Year Published

1979
1979
2012
2012

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(39 citation statements)
references
References 17 publications
2
34
2
1
Order By: Relevance
“…The results agree with the findings of the controlled environment studies that soybean seed yield increases as daily maximum temperature during seed development increases in cooler regions (Huxley et al, 1976;Sionit et al, 1987;Pan, 1996). At Hailun agroecosystem experiment station, the mean daily maximum temperature during seed fi lling varied from 20 to 24ºC over the study period which is within the maximum temperature range (18 to 30ºC) that gave maximum grain yield as found in the above studies.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The results agree with the findings of the controlled environment studies that soybean seed yield increases as daily maximum temperature during seed development increases in cooler regions (Huxley et al, 1976;Sionit et al, 1987;Pan, 1996). At Hailun agroecosystem experiment station, the mean daily maximum temperature during seed fi lling varied from 20 to 24ºC over the study period which is within the maximum temperature range (18 to 30ºC) that gave maximum grain yield as found in the above studies.…”
Section: Discussionsupporting
confidence: 82%
“…In order to adapt soybean systems to the increased daytime temperature, a comprehensive understanding of the impact during seed filling on soybean yield is warranted. Controlled environment chambers have proven that moderate increase in daytime temperature (18−26ºC) during seed fi lling benefi ted soybean yield (Sionit et al, 1987), but soybean yield decreased as daytime temperature increased above 26ºC (Huxley et al, 1976;Dornbos and Mullen, 1991;Gibson and Mullen, 1996). In the controlled experiments, daytime temperatures were held constant during seed filling; in contrast, daily maximum temperature in the fi elds varies daily and gradually decreases during the period.…”
mentioning
confidence: 99%
“…On the contrary, Saitoh et al (1998) found that the number of pods was closely correlated with the total number of fl oral buds but not with pods set. A high night temperature reduces seed yield (Huxley et al, 1976;Sato and Ikeda, 1979;Seddigh and Jolliff, 1984). Therefore, further research is required to determine the effects of air temperature on fl oral bud differentiation and pod setting as a limiting factor of seed yield in Xinjiang.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, pod number is considered to be one of the main factors for determining seed yield, and the variation in seed yield was often explained by pod number (Ikeda and Sato, 1990;Shimada et al, 1990;Board and Harvill, 1994;Wang et al, 1995;Saitoh et al, 1998). A high night air temperature has been reported to increase pod number (Gibson and Mullen, 1996;Zheng et al, 2002), but to reduce seed yield (Huxley et al, 1976;Sato and Ikeda, 1979;Seddigh and Jolliff, 1984). In this experiment, therefore, we examined the differences in growth among years in terms of the effect of air temperature on the growth parameters and pod setting, and to assume the conditions necessary to obtain a high yield in soybean in Xinjiang, China.…”
mentioning
confidence: 99%
See 1 more Smart Citation